Social and regional aspects of housing situation in Lithuania - Jonaitis, Vytautas; Naimavičiene, Jurga (International Journal of Strategic Property Management, 2010)
With respect to the assessment of Lithuanian housing situation in the context of other EU countries, it is important to consider it more thoroughly in social and regional aspects. It is also necessary to evaluate the situation on a scale of emerging housing problems and specify the strategic trends as well as goals to deal with these problems. This article discusses the following issues: social and regional aspects of housing and the quality of it; the possibility to obtain or rent a home in the context of current market situation; State financial support for housing; sociological assessment of living conditions.First Published Online: 18 Oct 2010